The DDX5/Dbp2 subfamily of DEAD-box RNA helicases - Xing, Zheng (Wiley Interdiscip Rev RNA, 2018)
The mammalian DEAD-box RNA helicase DDX5, its paralog DDX17, and their orthologs in Saccharomyces cerevisiae and Drosophila melanogaster, namely Dbp2 and Rm62, define a subfamily of DEAD-box proteins. Members from this subfamily share highly conserved protein sequences and cellular functions. They are involved in multiple steps of RNA metabolism including mRNA processing, microRNA processing, ribosome biogenesis, RNA decay, and regulation of long non-coding RNA activities. The DDX5/Dbp2 subfamily is also implicated in transcription regulation, cellular signalling pathways, and energy metabolism. One emerging theme underlying the diverse cellular functions is that the DDX5/Dbp2 subfamily of DEAD-box helicases act as chaperones for complexes formed by RNA molecules and proteins (RNP) in vivo. This RNP chaperone activity governs the functions of various RNA species through their life time. Importantly, mammalian DDX5 and DDX17 are involved in cancer progression when overexpressed through alteration of transcription and signalling pathways, meaning that they are possible targets for cancer therapy.